Comparison of firing stability between p‐ and n‐type polysilicon passivating contacts. (16th February 2022) - Kang, Di; Sio, Hang Cheong; Stuckelberger, Josua; Yan, Di; Phang, Sieu Pheng; Liu, Rong; Truong, Thien N.; Le, Tien; Nguyen, Hieu T.; Zhang, Xinyu; Macdonald, Daniel
Abstract: This work compares the firing response of ex‐situ doped p‐ and n‐type polysilicon (poly‐Si) passivating contacts and identifies possible mechanisms underlying their distinct firing behavior. The p‐type poly‐Si shows greater firing stability than n‐type poly‐Si, particularly at a higher firing temperature, which results in a substantial increase in the recombination current density parameter J 0 from 9 to 96 fA/cm 2 upon firing at 900°C for n‐type poly‐Si, in comparison to an increase from 11 to 30 fA/cm 2 for p‐type poly‐Si. It is observed that p‐type poly‐Si contacts only suffer a slight degradation or even exhibit a small improvement in J 0 after firing at 800°C, depending on the boron diffusion temperature. Secondary ion mass spectrometry (SIMS) results demonstrate that the hydrogen concentration near the interfacial SiO x increases with the peak firing temperature in n‐type poly‐Si, whereas the hydrogen profile remains unchanged for p‐type poly‐Si upon firing at various temperatures. Moreover, we observe that injecting additional hydrogen into the poly‐Si/SiO x stacks fired with SiN x coating layers further degrades n‐type poly‐Si, but recovers the J 0 of p‐type poly‐Si to the value before firing. In contrast, removing hydrogen from the fired poly‐Si/SiO x stacks leads to an initial recovery and then a second degradation of J 0 in n‐type poly‐Si, but no substantial impact on p‐type poly‐Si. It is hypothesized that the distinct difference in the firing impact on p‐ and n‐type poly‐Si is related to the different effective hydrogen diffusivity, which determines the hydrogen content surrounding the SiO x layer and hence the passivation quality after firing. Abstract : This work compares the thermal stability of ex‐situ doped p‐ and n‐type polysilicon passivating contacts. Injecting hydrogen into the fired sample further degrades n‐type polysilicon, but recovers p‐type polysilicon. In contrast, removing hydrogen leads to an initial recovery and then a degradation of J0 in n‐type polysilicon, but no substantial impact on p‐type polysilicon. One possible explanation for the different firing response could be the different effective hydrogen diffusivity.